Assessment of the breast volume by a new simple formula - Mahmoud, El-Oteify; Hosnia, Abdel Megeed; Bothaina, Ahmed; Mahmoud, El-Shazly (Indian Journal of Plastic Surgery, 2006)
Background: With the recent introduction of improved techniques for plastic surgery of the breast and increased public awareness toward these procedures, plastic surgeons are continuously trying to improve their methods and results to reach perfection. Assessment of the breast volume is an important issue prior to the use of breast implants in any aesthetic or reconstructive breast surgery. Previous methods to measure breast volume have included use of a simple bra and breast cup size, cumbersome fluid displacement, appliances and approximate visual estimation.Objectives: In this work we have tried to develop an easy method for assessment of the breast volume for both the patient and the the surgeon through a simple mathematical formula. Materials and Methods: Fifty two volunteers were included in this study. For every one, general parameters including age, weight and height were recorded. Local breast measurements and water volume displacement were also recorded. Results: The collected data were statistically correlated. Using the analyzed data, the breast volume was calculated through a simple and direct formula on the basis of the breast circumference. Conclusion: Our method has, as its principle, the use of an accurate and simple formula, which is based only on one measurement. This is easy for both the patient and the plastic surgeon. This equation is not only a significant technical advantage for the surgeon, but also provides a universal standardization of the breast volume.
Keywords: Breast; formula; volume